Arts and cultural participation among 17-year-olds - Smyth, Emer (ESRI, 2020)
Research, conducted by the ESRI and funded by the Arts Council, shows that young people become less involved in cultural activities as they prepare for the Leaving Certificate and leave school. Using data from the Growing Up in Ireland study, the report charts a decline in reading for pleasure and taking music/drama/dance lessons between 13 and 17 years of age.